Improving respiratory diagnostics (viruses) - Murdoch, David (Henry Stewart Talks, 2013)
Human respiratory viral infections, Community-acquired pneumonia in children, Viral pneumonia in adults (New Zealand), Diagnostic tools for respiratory viruses their accuracy –and developments – Various assays for respiratory viruses, Recently discovered respiratory viruses, Growth of the viral sequence database – Details of staged strategy for pathogen discovery including tests, analysis of findings & assigning causation